Potential Hepatoprotective Effect of Solanum xanthocarpum Against CCl4 Induced Hepatotoxicity in Albino Rats - Dheeba, B.; Sampathkumar, P.; Vijay, S.; Kannan, K.; Kannan, M. (Asian Journal of Chemistry, 2013)
The objective of current study is to assess the hepatoprotective effect of the ethanolic extract of Solanum xanthocarpum fruit in rat liver injured with carbon tetrachloride. The damage of the liver was studied in the experimental animals by assessing total protein, total bilirubin, cholesterol, serum glutamate oxaloacetate transaminase (SGOT), triglycerides, lactate dehydrogenase (LDH) and serum glutamate pyruvate transaminase (SGPT), in serum. The effect of co-administration of ethanolic extract of fruits of Solanum xanthocarpum (200 mg/Kg) on the above parameters was investigated. Hepatic damage was demonstrated with high levels of all parameters in serum of experimental animals which received carbon tetrachloride. The antioxidant assay of plant extract was proved against hydrogen peroxide and phospho molybdate assay. It is concluded that the fruits of Solanum xanthocarpum are rich in antioxidant and acts as a hepatoprotective agent and attenuates the hepatotoxic effect of carbon tetrachloride.